Quality management at Islamic school - Sigit Tri Utomo (IAIN Salatiga, 2018)
This research was aimed to give an understanding to stakeholders at educational institution especially Islamic institution in order to manage their institution by optimizing the potency they have. It is because a statement that a high quality school is a school that emphasize on good management within its insititution, administration, and human resource management. It was a descriptive qualitative research and used ovservation, interview, and documentation as the method of collecting data. To analyze the data, the researcher used data reduction because this research applied qualitative approach that was aimed to describe role of management at Muhammadiyah Vocational Scool of Bandongan Magelang Regency. Based on the result of research, Muhammadiyah Vocational School of Bandongan Magelang Regency used ISO 9001:2008 to manage the institution, it assummed that a good quality school will be reached easier and faster. Some attemps have been carried out for instance the alumni of this school have been transferred to interpreneurship or factories. Other attemps to reach high quality also have been tried by this institution to have better management by giving transparancy on every organization management, giving some sustainable training to improve professionality of personel management, and the whole quality of islamic school.